2012
DOI: 10.1111/ppa.12008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses to ultraviolet‐C radiation and methyl jasmonate in Pinus radiata seedlings that accompany induced resistance to Diplodia pinea

Abstract: Irradiation of Pinus radiata seedlings with ultraviolet-C (UV-C) radiation or spray application of methyl jasmonate (MeJA) each resulted in induced resistance to subsequent wound inoculation with Diplodia pinea. Induced resistance was expressed by lower incidence of disease and by reduced size of stem lesions than in untreated seedlings. UV-C was more effective than MeJA and the induced resistance was greatest in seedlings that were irradiated with UV-C for 60 min, 1 week before pathogen inoculation. Induced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…The sunflower and pine species were the most affected by UV-C radiation, decreasing their vigor and germinative power, with a high degree of deterioration in the pine seed. These results corroborate with those described by Reglinski et al [37], who demonstrated that the use of UV-C irradiation induces resistance to fungal infection in a conifer species (Pinus radiata). Similarly, Torres et al [38] and Cerero-Hernández [39] indicated that the percentage of normal plants in sunflowers was reduced when exposure to UV-C irradiation increased from 5 min to 60 min, which caused acute physiological stress, which led to a reduction in growth.…”
Section: Standard Germination Of Seeds Irradiated With Uv-csupporting
confidence: 92%
“…The sunflower and pine species were the most affected by UV-C radiation, decreasing their vigor and germinative power, with a high degree of deterioration in the pine seed. These results corroborate with those described by Reglinski et al [37], who demonstrated that the use of UV-C irradiation induces resistance to fungal infection in a conifer species (Pinus radiata). Similarly, Torres et al [38] and Cerero-Hernández [39] indicated that the percentage of normal plants in sunflowers was reduced when exposure to UV-C irradiation increased from 5 min to 60 min, which caused acute physiological stress, which led to a reduction in growth.…”
Section: Standard Germination Of Seeds Irradiated With Uv-csupporting
confidence: 92%
“…Jasmonates are known to induce physical and chemical defences in conifers, and MeJA application was shown to elevate concentrations of terpene and phenolic defence chemicals in radiata pine and to induce resistance against D. sapinea (Gould et al 2009) and also the large pine weevil Hylobius abietis (L.) (Zas et al 2014). Similarly, UV-C-induced resistance to D. sapinea in radiata pine was concomitant with increased activity of two defence-related enzymes, peroxidase and polyphenol oxidase (Reglinski et al 2013). Aside from crooking of the growing tip and needle death, infection of radiata pine with C. acutatum is also characterized by physiological symptoms including thickening of the stem and slowing down of apical growth (Nair and Corbin 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Global trends towards reduced fungicide use have broadened interest in alternative control options including biotic and abiotic agents that stimulate natural plant disease resistance (Eyles et al 2010;Reglinski et al 2014). Spray application of chitosan (Reglinski et al 2004) or methyl jasmonate (MeJA) (Gould et al 2008(Gould et al , 2009), or irradiation with UV-C (Reglinski et al 2013), has each been shown to enhance resistance of P. radiata seedlings against infection caused by the fungal pathogen Diplodia sapinea (Fr.) Fuckel (syn.…”
Section: Introductionmentioning
confidence: 99%
“…Diplodia pinea (D.pinea) is described as a pathogenic fungus capable of causing dieback, cankers, and tree death, in different Pinus species (Reglinski et al, 2013). The high incidence and severity of infection by D. pinea is associated with the spread of its spores by the action of rain and wind, in addition to being endophytic (asymptomatic condition) and transmitted by seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…The high incidence and severity of infection by D. pinea is associated with the spread of its spores by the action of rain and wind, in addition to being endophytic (asymptomatic condition) and transmitted by seedlings. Besides, these fungi have become more aggressive under periods of plant stress (drought, excessive rain, hail, or some injury to the plant) (Reglinski et al, 2013;Smith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%